Canada’s Egalitarian Debate - Zaretsky, Daniel (International Higher Education, 2012)
The Canadian university system, principally public and administered by its provinces, is distinct and telling in terms of societal trade-offs. Its most salient distinction in contrast to the United States is the absence of an Ivy League equivalent for undergraduate education, with emphasis on system-wide consistent high calibre and low tuition cost.